Commodification of Traditional Foods Namely Sate Lilit Bali in Spice Beach Club Bali - Rahmawati, Putu Indah; Artawan, Komang Agus; Widiastini, Ni Made Ary; Andiani, Nyoman Dini; Trianasari, Trianasari (Stupa, 2020)
This study aims to describe the commodification of traditional foods namely Sate Lilit Bali or Balinese type of Satay at the Spice Beach Club, Bali. This research uses a qualitative research approach. The object in this study is Sate Lilit, which is in the Spice Beach Club restaurant. Data collection methods used in this study were interviews, documentation, and observation. This study found that Spice Beach Club Lovina had commodified the Sate Lilit Bali to promote Balinese food and culture promotion without reducing the cultural value of Sate Lilit Bali. This study is important for a reference for further innovations in culinary art study in Hospitality Industry.